Alloys for molten-salt reactors - Azhazha, V.M.; Bakai, A.S.; Lavrinenko, S.D.; Bobrov, Yu.P.; V’yugov, P.N.; Kovtun, K.V.; Pylypenko, M.M.; Savchenko, V.I.; Solopikhin, A.D.; Stetsenko, S.P.; Malykhin, D.G. (Вопросы атомной науки и техники, 2005)
Results are reported from studies on the selection, development and manufacture of structural materials for a fuel-salt circulation loop of molten-salt reactors. Studies into the properties of materials obtained were performed. The analysis of the main physical properties has suggested the nickel-based alloy with the optimum composition. The basic initial components of the alloy were refined by physical methods. The influence of deformation and thermal treatment on structural and mechanical properties of melted alloys was investigated. The present results give grounds to advise the alloys under discussion as materials for the fuel loop of molten-salt reactors. Приведено результати досліджень по вибору, розробці та виготовленню конструкційних матеріалів для контуру циркуляції паливної солі рідинно-сольових реакторів і дослідження властивостей, отриманого матеріалу. Аналіз основних фізичних властивостей надав перевагу сплавам на основі нікелю. Вибрано оптимальний склад сплаву. Проведено рафінування фізичними методами основних вихідних компонентів сплаву. Вивчено вплив деформації та термомеханічної обробки на структурні та механічні властивості отриманих матеріалів. Отримані результати дозволяють рекомендувати ці сплави в якості матеріалів для паливного контуру рідинно-сольових реакторів. Приведены результаты исследований по выбору, разработке и изготовлению конструкционных материалов для контура циркуляции топливной соли жидко-солевых реакторов и исследованию свойств, полученного материала. Анализ основных физических свойств позволил выбрать сплав на основе никеля с оптимальным составом. Проведено рафинирование физическими методами основных исходных компонентов сплава. Изучено влияние деформации и термической обработки на структурные и механические свойства полученных материалов. Полученные результаты позволяют рекомендовать эти сплавы в качестве материалов для топливного контура жидко-солевых реакторов.